Visualisation of microalgal-viral interactions by high-speed atomic force microscopy - Evans, Christopher Thomas; Payton, Oliver; Picco, Loren; Allen, Michael J. (Frontiers in Virology, 2023)
Visualization of viruses and their hosts has been paramount to their study and understanding. The direct observation of the morphological dynamics of infection is a highly desired capability and the focus of instrument development across a variety of microscopy technologies. This study demonstrates progress that has been made in exploiting the capabilities offered by HS-AFM to characterise the interactions between coccolithoviruses and their globally important coccolithophore hosts. We observe whole Emiliania huxleyi Virus capsids, transient binding to Emiliania huxleyi derived supported lipid bilayers, and host-virus binding in real-time in an environmentally relevant, aqueous environment.